2015
DOI: 10.1073/pnas.1424804112
|View full text |Cite|
|
Sign up to set email alerts
|

MPE-seq, a new method for the genome-wide analysis of chromatin structure

Abstract: The analysis of chromatin structure is essential for the understanding of transcriptional regulation in eukaryotes. Here we describe methidiumpropyl-EDTA sequencing (MPE-seq), a method for the genome-wide characterization of chromatin that involves the digestion of nuclei withMPE-Fe(II) followed by massively parallel sequencing. Like micrococcal nuclease (MNase), MPE-Fe(II) preferentially cleaves the linker DNA between nucleosomes. However, there are differences in the cleavage of nuclear chromatin by MPE-Fe(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 59 publications
(70 reference statements)
6
85
1
Order By: Relevance
“…The extent to which these changes are due to nucleosomes themselves as opposed to nonhistone proteins has been a matter of recent debate (Chereji et al 2017). In larger eukaryotes, fragile nucleosomes upstream of TSSs have been found in Drosophila (Chereji et al 2016, Mieczkowski et al 2016) and human embryonic stem cells (Ishii et al 2015;Voong et al 2016), but whether these seemingly ubiquitous features of eukaryotic promoters are true nucleosomes or other DNA-binding proteins remains to be determined. To address whether nucleosomes were responsible for protection in the work presented here, the experiments were all performed with a histone H3 immunoprecipitation step to indicate that all measured fragments contained nucleosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which these changes are due to nucleosomes themselves as opposed to nonhistone proteins has been a matter of recent debate (Chereji et al 2017). In larger eukaryotes, fragile nucleosomes upstream of TSSs have been found in Drosophila (Chereji et al 2016, Mieczkowski et al 2016) and human embryonic stem cells (Ishii et al 2015;Voong et al 2016), but whether these seemingly ubiquitous features of eukaryotic promoters are true nucleosomes or other DNA-binding proteins remains to be determined. To address whether nucleosomes were responsible for protection in the work presented here, the experiments were all performed with a histone H3 immunoprecipitation step to indicate that all measured fragments contained nucleosomes.…”
Section: Discussionmentioning
confidence: 99%
“…A prior nucleosome mapping study, using relatively high levels of MNase digestion, reported no differences in nucleosome occupancy at selected sites in the absence of FoxA1 and FoxA2, possibly because nucleosomes at open chromatin regions had been missed (Li et al, 2011). A recent study, using substantially lower levels of chromatin digestion with methidiumpropyl-EDTA coupled with core histone ChIP, revealed more apparent nucleosome retention than had been revealed by prior high-level MNase studies (Ishii et al, 2015). In yeast, low levels of MNase digestion recovered DNA fragments within previously determined “nucleosome-free” regions (200 bp upstream of the TSS) in a subset of promoters in addition to within the −1 nucleosome position (upstream of the “nucleosome-free” region), and renamed them as “fragile nucleosomes” (Rhee et al, 2014; Weiner et al, 2010; Xi et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Second, prenucleosome-sized DNA-containing particles with core histones are observed at the NDRs of active promoters in mouse cells (Fig. 7; also see Ishii et al 2015). Moreover, the occurrence of these particles correlates with the level of promoter activity.…”
Section: Summary and Perspectivesmentioning
confidence: 90%
“…To gain a different perspective on chromatin structure, we used the chemical reagent methidiumpropyl-EDTA-Fe(II) (MPE-Fe(II)) to cleave chromatin in nuclei, and then we analyzed the resulting DNA fragments by genome-wide paired-end sequencing (Ishii et al 2015). This method, termed MPE-seq, revealed that the upstream promoter regions of active genes in mouse cells contain chromatin particles with subnucleosome-sized DNA fragments.…”
Section: Mpe-seq Reveals Prenucleosomelike Particles At the Upstream mentioning
confidence: 99%
See 1 more Smart Citation